THERMOSTABLE RECOMBINANT PHYTASE PRODUCED IN E. COLI - Yevtykhova, Y.B.; Silaev, D.V.; Baltabekova, A.J.; Shustov , A.V. (Eurasian Journal of Applied Biotechnology, 2014)
One of the main challenges for the Kazakhstan’s livestock and fodder industry is improvement of food supply and increase in feed efficiency. A cost effective way to improve the quality of animal feed is to mobilize bound phosphate from indigestible plant components. Particular feed additives, namely phytases are able to solve this problem. Phytases are enzymes that break down the phytic acid, which is main storage form of phosphorus in plants. This paper describes a method of producing a recombinant thermostable phytase. Phytase Nov9x is a derivative of E.coli phytase AppA with improved thermostability which is an important industrial quality. Compared to the parental phytase AppA, the Nov9x sequence has eight mutations. Synthetic gene for recombinant thermostable phytase Nov9x was designed in silico and synthesized de novo from an array of long oligonucleotides. The assembled gene was sequence-verified. Expression constructs were obtained based on the Novagen vectors for bacterial expression, pET22 and pET32. An E.coli strain BL21(DE3) transformed with the pET22/Nov9x plasmid did not produced significant amounts of the recombinant protein. Efficient expression of the recombinant protein was observed for same strain transformed with the pET32/Nov9x plasmid. In the latter case the expression product is a fusion protein bearing a sequence of E.coli thioredoxin on the N-terminus and a sequence of phytase (Nov9x) at the C-terminus. Recombinant phytase was purified by metal chelate chromatography. The yield of purified recombinant phytase was 2,1 milligram from 200 ml of induced culture. Specific enzymatic activity of the purified phytase was 3344 FTU per 1 mg of protein. Biochemical investigations with the recombinant phytase included determination of the pH- and temperature-dependence of activity and description of thermostability. Obtained phytase demonstrated highest activity in a pH range of 4,5-6,0. Particularly, the recombinant phytase retains at least 20% from maximum activity at pH 1,5 corresponding to most acidic parts of the stomach. The recombinant phytase has high thermal stability: it retains 75% of activity after incubation at 60°C for 2 hours, or 29% of activity after incubation at 70°C for 30 min. Addition of protectant to the probes further improves the thermostability of phytase: in presence of 1 mg/ml gelatine the recombinant phytase retains 50% of activity after incubation at 70°C for 2 hours. The described gene of thermostable phytase, bacterial strain transformed with expression plasmid and the recombinant enzyme, all have prospects of utilization in production of additives for the livestock and poultry fodder.